THE IMPACT OF FINANCIAL LITERACY, FINANCIAL BEHAVIOR, AND INCOME ON FINANCIAL PLANNING FOR CHILD’S EDUCATION FUNDS - Bayu Tri Cahya; Ika Erlita; Ibnu Muttaqin (Jurnal Studi Gender dan Anak, 2023)
This study aims to determine the effect of financial literacy, financial behavior, and income on financial planning in children's education funds. This type of research is quantitative research with causal methods. The population of this study is housewives who live in Kotakan Village, Karanganyar District, Demak Regency. The sampling technique used was purposive sampling and a sample of 95 respondents was obtained. Data collection techniques using a questionnaire. The analytical method used is multiple linear regression analysis with SPSS 25 software. The results of the study state that financial literacy has a positive and significant effect on financial planning in children's education funds. Income has a positive and significant effect on financial planning in children's education funds. Financial behavior has a positive and insignificant effect on financial planning in children's education funds.